REACTION KINETICS OF 1,4-DIAMINOBUTANE WITH DIMERICFATTY ACIDS - Mohammad, H .; Falah, A .; Hammoy, M . (Iraqi Journal of Science, 2024)
Kinetic studies were carried out on the reaction between 1,4-Diaminobutaneanddimeric fatty acids in melt phase . The reaction was performed at 123, 138, 146,160, and 170 ºC and followed by determining the acid value of the product .Thepolyamidation reaction was found to be of overall second order with an activationenergy of 28.18kJ mol-1up to 85% conversion and overall third order above 85%conversion .The Degree of Polymerization ,Number Average Molecular Weight,Weight Average Molecular Weight has been calculated during different times , Therelationships between Degree of Polymerization ,Number Average MolecularWeight, Weight Average Molecular Weight with the times is linear until85%conversion ,The Refractive index of polyamide solution was measured at differenttemperatures.